Mobility Deficits Assessed With Mobile Technology: What Can We Learn From Brain Iron-Altered Animal Models? - Hopfner, Franziska; Hobert, Markus A.; Maetzler, Corina; Hansen, Clint; Pham, Minh Hoang; Moreau, Caroline; Berg, Daniela; Devos, David; Maetzler, Walter, The Fair-Park II study group (Frontiers in Neurology, 2019)
BACKGROUND: Recent developments in mobile technology have enabled the investigation of human movements and mobility under natural conditions, i.e. in the home environment. Iron accumulation in the basal ganglia is deleterious in Parkinson’s disease (i.e. iron accumulation with lower striatal level of dopamine). The effect of iron chelation (i.e. re-deployment of iron) in Parkinson’s disease patients is currently tested in a large investigator-initiated multicenter study. Conversely, restless legs syndrome is associated with iron depletion and higher striatal level of dopamine. To determine from animal models which movement and mobility parameters might be associated with iron content modulation and the potential effect of therapeutic chelation inhuman. METHODS: We recapitulated pathophysiological aspects of the association between iron, dopamine and neuronal dysfunction and deterioration in the basal ganglia, and systematically searched PubMed to identify original articles reporting about quantitatively assessed mobility deficits in animal models of brain iron dyshomeostasis. RESULTS: We found six original studies using murine and fly models fulfilling the inclusion criteria. Especially postural and trunk stability were altered in animal models with iron overload. Animal models with lowered basal ganglia iron suffered from alterations in physical activity, mobility and sleep fragmentation. CONCLUSION: From preclinical investigations in the animal model, we can deduce that possibly also in humans with iron accumulation in the basal ganglia undergoing therapeutic chelation may primarily show changes in physical activity (such as daily “motor activity”), postural and trunk stability and sleep fragmentation. These changes can readily be monitored with currently available mobile technology. deficits in animal models of brain iron dyshomeostasis. RESULTS: We found six original studies using murine and fly models fulfilling the inclusion criteria. Especially postural and trunk stability were altered in animal models with iron overload. Animal models with lowered basal ganglia iron suffered from alterations in physical activity, mobility and sleep fragmentation. CONCLUSION: According to preclinical data, humans with iron accumulation in the basal ganglia undergoing therapeutic chelation may primarily show changes in physical activity (such as daily “motor activity”), postural and trunk stability and sleep fragmentation. These changes can readily be monitored with currently available mobile technology.